Oxytocinergic Feedback Circuitries: An Anatomical Basis for Neuromodulation of Social Behaviors - Lefevre, Arthur; Benusiglio, Diego; Tang, Yan; Krabichler, Quirin; Charlet, Alexandre; Grinevich, Valery (Frontiers in Neural Circuits, 2021)
Oxytocin (OT) is a neuropeptide produced by hypothalamic neurons and is known to modulate social behavior among other functions. Several experiments have shown that OT modulates neuronal activity in many brain areas, including sensory cortices. OT neurons thus project axons to various cortical and subcortical structures and activate neuronal subpopulations to increase signal-to-noise ratio, and in turn increases the saliency of social stimuli. Less is known about the origin of inputs to OT neurons, but recent studies show that cells projecting to OT neurons are located in regions where the OT receptor (OTR) is expressed. Thus, we propose the existence of a reciprocal connectivity between OT neurons and extrahypothalamic OTR neurons to tune OT neuron activity depending on the behavioral context. Furthermore, latest studies have shown that OTR-expressing neurons located in social brain regions project to other social brain regions containing OTR-expressing neurons. We hypothesize that OTR-expressing neurons across the brain constitute a common network coordinated by OT.